A pathophysiological intersection between metabolic biomarkers and memory: a longitudinal study in the STZ-induced diabetic mouse model - Venuti, Maria Teresa; Roda, Elisa; Brandalise, Federico; Sarkar, Meghma; Cappelletti, Mattia; Speciani, Attilio F.; Soffientini, Irene; Priori, Erica Cecilia; Giammello, Francesca; Ratto, Daniela; Locatelli, Carlo A.; Rossi, Paola (Frontiers in Physiology, 2025)
Diabetes mellitus (DM) is a metabolic disorder characterized by high blood sugar levels due to insufficient insulin production or insulin resistance. Recently, metabolic biomarkers, such as glycated albumin (GA) and methylglyoxal (MGO), have been successfully employed for the management of diabetes and its complications. The main goal of this study was to investigate the relationship between metabolic parameters, related to diabetic conditions, and the recognition memory, a declarative episodic long-term memory, in a streptozotocin (STZ)-induced diabetes mouse model. The longitudinal experimental plan scheduled five experimental timepoints, starting from 9 months and lasting until 19 months of age, and included different evaluations: i) fasting serum glucose, GA, and MGO, ii) recognition memory performance; iii) histological examinations of pancreas and hippocampus. At 13 months of age, mice were randomly divided into two groups, and STZ (50 mg/kg i.p.) or vehicle was administered for 5 consecutive days. Mice were fed with a normal diet but, starting from 14 months, half of them were given water with a high sugar (HS) to explore the potential detrimental effects of HS intake to hyperglycemia. Our main outcomes are as follows: i) HS intake alone does not contribute to worsened diabetic condition/hyperglycemia; ii) GA emerges as a reliable biomarker for monitoring diabetic conditions, consistently increasing with hyperglycemia; iii) diabetic conditions correlate with a worsening of recognition memory; iv) diabetic mice display mild-to-severe insulitis and injured hippocampal cytoarchitecture, detectable in Ammon’s horns regions CA1 and CA3; v) correlation among recovered normal fasting glycemic level and recognition memory, partial regaining of physiological pancreatic morphology, and hippocampal cytoarchitecture.